Reducing “white elephant” ICT4D projects: A Community Researcher Engagement - Tariq, Zaman; Yeo, Alvin Wee; Heike, Winschiers-Theophilus (ACM International Conference Proceeding Series, 2015)
Participation is a key requirement to ensure that ICT4D and HCI4D projects succeed. Specifically, the relationship between the research and community is necessary for any ICT4D project; without this cooperation, the proverbial white elephant project will result. Existing literature provides much evidence on the need and importance of this participation. However, many researchers lack the skills and knowledge to be able to build, develop and maintain the relationship, as many interactions are based on assumptions. We investigate challenges and frustrations as expressed by a community with whom we have established a long term collaboration. This provides further evidence on the need to guide and educate novice researchers working with the community. We have conducted a workshop to raise the awareness among guest researchers. The workshop comprises a series of presentations, discussions and reflections. We have recorded guest researchers’ responses within the workshop to evaluate further needs for researcher-community interaction preparations. A workshop is yet only one of the gatekeepers’ obligations to protect the community. We equally promote continuous engagement with the community itself in the design of critical incidents based on established cultural protocols as well as preparing the community for the novice researchers to maximize research benefits to the community. We discuss potential roles and responsibilities of all stakeholders, partner community, gatekeepers and guest researchers aiming to sustain a coherent research and development collaboration.